A Characterization of the Dirichlet Distribution with Application to Learning Bayesian Networks - Geiger, Dan; Heckerman, David (1995)
We provide a new characterization of the Dirichlet distribution. This characterization implies that under assumptions made by several previous authors for learning belief networks, a Dirichlet prior on the parameters is inevitable.
Real-Time Graphics Architectures, Algorithms, and Programming Systems: Project Technical Report